Cohort-level sex ratio effects on women's labor force participation - Shoshana Amyra Grossbard; Catalina Amuedo-Dorantes (Institute for the Study of Labor (IZA), 2007)
It follows from a number of theoretical models of marriage that the scarcer women are relative to men, i.e. the higher the sex ratio, the less married women are likely to participate in the labor force. Such sex ratio effects may be stronger among less educated women. These predictions are tested using individual data from Current Population Surveys for four regions of the U.S. (Northeast, Midwest, South and West), and for the U.S. as a whole, covering the period 1965 to 2005 at five-year intervals. Within-region sex ratio variation results from variation in cohort size (due principally to large fluctuations in number of births) and limited fluctuations in the difference between male and female age at marriage. As hypothesized, we find that sex ratios are inversely related to women's labor force participation, reflecting that ceteris paribus women born in years of peak baby-boom are more likely to be in the labor force than women born in years of peak baby-bust. Additionally, weaker sex ratio effects are found among educated women in two of the four regions of the United States.
urn:nbn:de:101:1-20080402521
Keywords: 330; Geschlecht; Bevölkerungsstruktur; Frauenerwerbstätigkeit; USA